Ciągłość i zmiana profilu zielonogórskich instytucji kultury = Continuity and change in the profile of Zielona Góra`s cultural institutions - Idzikowski, Bogdan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper discusses the results of the empirical research covering 17 of Zielona Góra`s cultural institutions run in the spring of 2007 with a structural interview method. The key concepts are: disciplines of symbolic culture, social functions, continuity and change, programme profile.
Keywords: Zielona Góra; instytucje kultury